Syntactic and Semantic Parallelism in Ptolemaic Hieroglyphic Texts - Madkour, Haitham (Zeitschrift für ägyptische Sprache und Altertumskunde, 2022)
This article presents a linguistic analysis of parallelism as a stylistic device in Ptolemaic hieroglyphic texts. It concentrates on the syntactic and semantic parallelism, using different texts from the Ptolemaic and Roman temples.